3‐D Characterization of Detrital Zircon Grains and its Implications for Fluvial Transport, Mixing, and Preservation Bias. (26th December 2017) - Markwitz, V.; Kirkland, C. L.; Mehnert, A.; Gessner, K.; Shaw, J.
Abstract: Detrital zircon studies can suffer from selective loss of provenance information due to U‐Pb age discordance, metamictization, metamorphic overprinting and fluviatile transport processes. The relationship between isotopic composition and zircon grain shape, and how grain shape is modified during transport, is largely unknown. We combine X‐ray tomography with U‐Pb geochronology to quantify how fluvial transport affects 3‐D zircon shape, detrital age signature, and grain density along the Murchison River, whose catchment comprises Eoarchean to Early Paleozoic source rocks in Western Australia. We acquired tomographic volumes and isotopic data from 373 detrital zircons to document changes in size, shape and density in transport direction, and explore how grain shape, age spectra and the proportion of discordant material vary along the channel. Results show that shape characteristics are sensitive to transport distance, stream gradient, proximity to source material, and whether the source consists of primary or recycled zircons. With increasing transport distance, grain lengths decrease more than their widths. Furthermore, the loss of metamict grains occurs at a near constant rate, resulting in a linear increase of mean calculated zircon density by ca. 0.03 g/cm 3 per 100 km transport distance. 3‐D grain shape is therefore strongly linked to detrital age signature, and mean grain density is a function of the absolute transport distance. 3‐D shape characteristics provide valuable information on detrital zircon populations, including the interaction between source materials with fluvial transport processes, which significantly affects preservation bias and, by inference, the representativeness of the sampled data. Key Points: First application of X‐ray tomography to analyze zircon grain shape 3‐D quantification of grain surface roughness and sphericity 3‐D grain shape relates to source proximity, channel gradient and transport distance